2010
DOI: 10.1159/000298820
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronously Replicating Eu/Heterochromatic Regions Shape Chromosome Damage

Abstract: In order to shed more light on the influence of DNA replication on the formation and distribution of chromosome aberrations, breakpoints (BP) produced by UV-C and AluI were assigned either to the early replicating short euchromatic arm (Xpe) or to the late replicating long heterochromatic arm (Xqh) of the Chinese hamster (CHO9) X chromosome. Early (ES) or late (LS) S-phase cells were assessed by pulse incorporating the base analogue 5-bromo-2′-deoxyuridine (BrdU) immediately after UV-C ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Chromosome segments close to centromeres showed low γH2AX signaling (sign-test, p < 0.0001) with a tendency to increase towards distal regions (Figure 3). This uneven γH2AX signal distribution between chromosomes and chromosome regions is in agreement with the inter-and intra-chromosomal variability of the induced-damage reported by researchers of our laboratory in CHO cells [46]- [52] and others [53]- [61] both in human and in other mammalian cells.…”
Section: Blm-induced γH2ax Signals Differed Between Chromosomes and Psupporting
confidence: 92%
“…Chromosome segments close to centromeres showed low γH2AX signaling (sign-test, p < 0.0001) with a tendency to increase towards distal regions (Figure 3). This uneven γH2AX signal distribution between chromosomes and chromosome regions is in agreement with the inter-and intra-chromosomal variability of the induced-damage reported by researchers of our laboratory in CHO cells [46]- [52] and others [53]- [61] both in human and in other mammalian cells.…”
Section: Blm-induced γH2ax Signals Differed Between Chromosomes and Psupporting
confidence: 92%
“…Xp/Xq BP localization showed that when Xp replicates, BP produced by either MMS, UV-C or etoposide clustered in Xp. On the other hand, during Xq replication, BP induced by the clastogens concentrated in Xq [91,92] (Figure 6). Since UV-C and MMS are S-phase dependent clastogens, the observed predominance of BP produced in Xp or Xq according to replication timing could be explained based on their requirement of DNA synthesis to produce CA.…”
Section: The Application Of χ 2 Test To Analyze the Association Betwementioning
confidence: 99%
“…Besides, Xq replicates in late S-phase whereas the euchromatin of the short arm (Xp) and the Xq secondary constriction duplicates during early S-phase ( Figure 5) [89,90]. Differential replication timing of Xp and Xq of CHO cells provided a valuable experimental model to analyze the relationship between eu/heterochromatin DNA replication and CA induced by different types of clastogens: UV-C light, the methylating agent methylmethane sulphonate (MMS) and the anti-topoisomerase II inhibitor etoposide (a cleavable complex trapper) in BrdU pulse-labeled CHO9 chromosomes [91,92].…”
Section: Eu/heterochromatin Replication and Induced-damage Distributimentioning
confidence: 99%
See 2 more Smart Citations